Mirrors and Self-Representation in the Age of Digital Hyper-Mediation - Flechoso Fernández, Rodrigo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This text aims to compare the experience in front of the mirror with that maintained with the virtual platforms we interact with on a daily basis (such as web 2.0 or social networks). Both devices play an intermediary role in the image that they give back to us and that has a great impact on the construction of our identity. By analyzing the symbolic and morphological characteristics they share, we can see to what extent they are determinant for the nature of the reflection they emit, revealing the alarming loss of control that individuals have over their own subjectivity.